Delo s povzročitelji nasilja - Hrovat, Tjaša (Socialno delo, 2016)
Preventing and stopping violence requires an integrated approach of various institutions, with an emphasis on rapid intervention. The article presents the essential features of the work with perpetrators of violence, which is not limited to specialized programmes. It includes all forms of establishing a relationship with perpetrators of violence. Every professional worker must consider at least some of the basic principles of work with perpetrators and communicate uniform and straightforward messages to them. It is also important to make Violence Risk Assessment, which is a base for Personal Responsibility Plan, created by a professional worker and a perpetrator. Working with perpetrators of violence is difficult both professionally and personally. Therefore professional workers must be appropriately trained and are expected to have regular supervision and intervision.
Keywords: nasilje; risk assessment; intervention; analiza tveganja; intervencija; professionals; strokovnjaki